Research Progress on the Impact of Land Use and Climate Change on Gully Runoff in Yan' an City - Yang, Liangyan; Shi, Lei (International Journal of Natural Resources and Environmental Studies, 2025)
The ArcSWAT model provides an effective tool for quantifying the responses of gully runoff in Yan'an City to land use and climate change. Returning farmland to forest and reclaiming land from gullies have significantly reduced soil erosion through vegetation restoration and engineering measures. However, climate change may offset some of the ecological benefits. The vegetation index of Yan'an City from 2000 to 2019 ranged from 0.54 to 0.75. In terms of time distribution, it showed a significant upward trend, with an overall upward rate of 0.095/(10a). From 2000 to 2019, 79.83% of the regional vegetation in Yan'an City showed an improving trend, mainly distributed in the loess ridges and gully areas in the north and east of Yan'an City. The degraded areas accounted for 0.34% of Yan'an City, mainly distributed in the urban area of Yan'an City and the suburban areas of county-level cities, presenting a point-like and strip-like distribution. From 2000 to 2012, human activities were the dominant factor determining the status of vegetation index. From 2013 to 2019, the main factors affecting the growth of vegetation in Yan'an were water and heat conditions. In the future, strategies for land use optimization, engineering maintenance and climate adaptability need to be comprehensively considered to achieve the coordinated goal of ecological protection and sustainable utilization of water resources.